Cocoa Cultivation in Northeast Region - S, Elain Apshara; L S, Singh; Uchoi, Anok; Das, Alpana; Patel, V B (Indian Horticulture, 2024)
INDIA has vast potential to promote cocoa in Northeast region, where the agro climatic condition is suitable with high rainfall, short dry spell and sub tropic humid climate. Palms and local, native, region specific fruit/ forest trees are also available which provide 50% shade required by cocoa and accommodate it as agro-forestry system as well. Realizing its potential, the Ministry of Agriculture & Farmers Welfare, GoI, has proposed an area of 50,000 ha to be expanded in Northeast region. With this background, this article analyzed the scope and prospects of cocoa in Northeast region.